Експлуатаційні режими руху транспортних засобів у місті Львові - Качмар, Роман (КІНПАТРІ ЛТД, 2013)
The analysis of modes of transport traffic in different operating conditions and existing driving cycles countries, the analysis of the results of research and determined the main features of the operating modes of movement of vehicles of the city, developed methodology for benchmarking existing and developed driving cycles performed analysis of existing and developed driving cycles.
Operational modes of vehicular traffic in Lviv